LIST OF MATERIALS PUBLISHED IN THE RUSSIAN JOURNAL OF CARDIOLOGY FOR THE YEAR 2000 (Российский кардиологический журнал, 2000)
List of materials published in the Russian Journal of cardiology for the year 2000.